A INTEGRAÇÃO DA PESQUISA E DOS EXPERIMENTOS PRÁTICOS AOS CONTEÚDOS DE FÍSICA E QUÍMICA DO ENSINO MÉDIO - Weber, Samantha; Schio, Fernando; Lena, Diego; Guimarães, Gil E.; Pereira, Jean C. B. (Salão do Conhecimento, 2013)
Resumo